2017
DOI: 10.1210/jc.2017-00682
|View full text |Cite
|
Sign up to set email alerts
|

Response to Antenatal Cholecalciferol Supplementation Is Associated With Common Vitamin D–Related Genetic Variants

Abstract: Context:Single-nucleotide polymorphisms (SNPs) in genes related to vitamin D metabolism have been associated with serum 25-hydroxyvitamin D [25(OH)D] concentration, but these relationships have not been examined following antenatal cholecalciferol supplementation.Objective:To determine whether SNPs in DHCR7, CYP2R1, CYP24A1, and GC are associated with the response to gestational cholecalciferol supplementation.Design:Within-randomization group analysis of the Maternal Vitamin D Osteoporosis Study trial of ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 28 publications
7
45
4
Order By: Relevance
“…Moreover, within the Gc2 polymorphic region (rs4588), individuals in an Iranian population with an AA genotype within this polymorphic region showed a greater increase in 25(OH)D levels following vitamin D supplementation than those with the GG genotype did (47). Similar results were found with a different polymorphism at rs2282679 in Caucasian women (48). Rs2282679, an intronic polymorphism in the DBP gene that does not alter DBP structure, was previously shown in GWAS studies to be associated with lower 25(OH)D and DBP levels in several different populations (49)(50)(51).…”
Section: Biologic Functionsupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, within the Gc2 polymorphic region (rs4588), individuals in an Iranian population with an AA genotype within this polymorphic region showed a greater increase in 25(OH)D levels following vitamin D supplementation than those with the GG genotype did (47). Similar results were found with a different polymorphism at rs2282679 in Caucasian women (48). Rs2282679, an intronic polymorphism in the DBP gene that does not alter DBP structure, was previously shown in GWAS studies to be associated with lower 25(OH)D and DBP levels in several different populations (49)(50)(51).…”
Section: Biologic Functionsupporting
confidence: 57%
“…DBP is comprised of 3 structurally similar domains. The first domain is the binding site for the vitamin D metabolites (aa [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. Fatty acid binding utilizes a single high affinity site for both palmitic acid and arachidonic acid, but only arachidonic acid competes with 25(OH)D for binding (16,17).…”
Section: Structure and Polymorphismsmentioning
confidence: 99%
“…The results of this trial suggest that such a supplementary approach leads to improved offspring bone mineral content (of around 0.5 SD) compared with placebo, for neonates born in the winter months, when background 25(OH)D concentrations are lowest (although not in the population overall) . Subsequent work has identified interactions with both environmental and genetic factors in the achieved 25 (OH)D in response to treatment (Moon et al , 2017; mechanistic investigations using placental samples have identified novel relationships between vitamin D and placental nutrient transport (Cleal et al 2015). These candidate-focused studies contrast with findings from a recent investigation using the Illumina Human Methylation 450 BeadChip, an array covering methylation marks at over 450 000 CpG sites across the genome.…”
Section: Epigenetic Predictors Of Childhood Bone Healthmentioning
confidence: 99%
“…Subsequent work has identified interactions with both environmental and genetic factors in the achieved 25(OH)D in response to treatment (Moon et al . , ); mechanistic investigations using placental samples have identified novel relationships between vitamin D and placental nutrient transport (Cleal et al . ).…”
Section: Dna Methylation and Bone Development: Potential Roles In Latmentioning
confidence: 99%
“…This dose is sufficient for the general population who adequately expose themselves to the sun, but it is too low to treat situations of vitamin D deficiency, especially in mothers and newborns with genetic variation in genes involved in vitamin D metabolism [22], or with a goal to achieve vitamin D levels higher than 30 ng/mL. In fact, some health organizations suggest that at least 400 IU/day is used as a supplement, and the total intake should be in the range of 1,000-2,000 IU/day from dietary sources (e.g., oily fish) and supplements [23].…”
Section: Vitamin D Intake Recommendations During Pregnancymentioning
confidence: 99%